Designing a Model to Measure Customer Satisfaction for Municipality Services in Iran - Hamid Reza Fooladgar; Abbas Saghaee (International Journal of Supply Chain Management, 2022)
One of the most crucial changes which occurred in the domain of improvement of quality in the last decade of the 20th Century was the introduction of a system to measure the level of customer satisfaction as one of the main requirements or components of quality management services for entire business institutions and agencies. The objective of this study is to design and constitute a system capable of measuring the rate of satisfaction among customers which in particular can be applied in municipalities. The statistical pool of the current research is divided in two groups: First, are university professors and experts qualified. Second, are municipalities customers. The method of data collection determined for the first group was non-probability and random sampling and the scope and limitation of this data was specified through the application of the central limit theorem. The sampling method used for the second group was random regional sampling through the application of the proportional distribution method. Hypotheses testing was carried out by applying tests of variations analysis, analysis of the confirmatory factor and structural equation modelling using SPSS, LISREL and PLS software. Conclusion of the study indicates a significant, positive impact of processes involving services offered by the city (municipality) the perceived quality of services. In addition, the significant and positive impact of the concept of quality service an average customer conceives regarding the perceived level of service quality is also confirmed. Furthermore, the significant and positive impact of a mutual comprehension of the effect of quality on customer satisfaction has been confirmed and it has also been verified that the range of customer expectations has a direct significant and positive impact on the level of customer satisfaction. Finally, the role of a significant and positive impact on customer satisfaction in promoting customer trust has also been confirmed.